Molecular identification and physiological functional analysis of NtNRT1.1B that mediated nitrate long-distance transport and improved plant growth when overexpressed in tobacco - Wu, Changzheng; Xiang, Yucheng; Huang, Pingjun; Zhang, Mingfa; Fang, Ming; Yang, Weiqin; Li, Wenrui; Cao, Fengchun; Liu, Lai-Hua; Pu, Wenxuan; Duan, Shuhui (Frontiers in Plant Science, 2023)
Although recent physiological studies demonstrate that flue-cure tobacco does preferentially utilize NO3- or NH4NO3 and possess both high- and low-affinity uptake systems for NO3-, little is known about a molecular component(s) responsible for NO3- acquisition and translocation in this crop. Here we provided experimental data showing that NtNRT1.1B with 1785bp coding-sequence exhibited indeed a functionality in mediating NO3- transport associated with tobacco growth on NO3--nutrition. Heterologous expression of NtNRT1.1B in NO3--uptake-defective yeast Hp△ynt1 enabled a growth recovery of the mutant on 0.5 mM NO3-, suggesting a possible molecular action of NtNRT1.1B for NO3- import into cells; transient expression of NtNRT1.1B::GFP in tobacco leaf cells revealed a main targeting of NtNRT1.1B to the plasma-membrane, proposing a possibility of NO3- permeation across cell membrane via NtNRT1.1B. Furthermore, promoter activity assays using GFP-marker clearly indicated that NtNRT1.1B transcription in roots may be down-regulated by N-starvation and induced by N-resupply including NO3- after 3d N-depletion. Significantly, a constitutive overexpression of NtNRT1.1B could remarkably enhance tobacco growth by showing a higher accumulation of biomass and total N, NO3- and even NH4+ in plants supplied with NO3-; this NtNRT1.1B-facilitated more N acquisition/accumulation could be strengthened by a short-term 15N-NO3- root-influx assays, which showed a 15-20% higher NO3--deposition in NtNRT1.1B-overexpressors as well as a high affinity of NtNRT1.1B for NO− 3 at a Km of around 30-45 µM. Together with detection of NtNRT1.1B promoter activity in root stele and shoot-stem vascular tissues, and higher NO3- in both xylem exudate and apoplastic-washing-fluid of NtNRT1.1B-transgenic lines, NtNRT1.1B would be considered as a valuable molecular-breeding target aiming at improving crop N-use efficiency by manipulating the absorption and long-distance distribution/transport of nitrate, thus adding a new functional homolog as a nitrate permease to the plant NRT1 family.